1999
DOI: 10.1111/j.1540-8167.1999.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Effects of Selective Right versus Left Atrial Linear Lesions in a Canine Model of Chronic Atrial Fibrillation

Abstract: Left atrial linear lesions affect right atrial endocardial activation, whereas right atrial lesions do not affect left atrial activation in a canine model of atrial fibrillation. These findings suggest that the left atrium is the driver during chronic atrial fibrillation in this animal model and may explain the limited success of right atrial ablation alone in human atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…Most importantly, LA ablation increased the cycle length on the RA, whereas RA ablation had no appreciable effect on LA AF cycle length, supporting our idea 6 -8 that the LA is the primary driver during AF, at least in some cases. Our results, together with those of Roithinger et al, 28 open potentially exciting new possibilities for targeting LA sources for therapies, whether ablative, electrical, pharmacological, or hybrid.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Most importantly, LA ablation increased the cycle length on the RA, whereas RA ablation had no appreciable effect on LA AF cycle length, supporting our idea 6 -8 that the LA is the primary driver during AF, at least in some cases. Our results, together with those of Roithinger et al, 28 open potentially exciting new possibilities for targeting LA sources for therapies, whether ablative, electrical, pharmacological, or hybrid.…”
Section: Discussionsupporting
confidence: 70%
“…Other studies demonstrated a greater rate of success of LA radiofrequency (RF) ablation (60% to 80%) 12,26,27 than of RA ablation to eliminate AF. In a recent study by Roithinger et al, 28 single RA and LA RF ablation caused prolongation of AF cycle length in the ablated atrium. Most importantly, LA ablation increased the cycle length on the RA, whereas RA ablation had no appreciable effect on LA AF cycle length, supporting our idea 6 -8 that the LA is the primary driver during AF, at least in some cases.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies 27,28 have attached particular importance to the left atrium in the initiation and maintaining of AF and the present study showed that there were aging-associated changes of the electrophysiological properties of the atrial myocardium. In the aged group there was a shorter MAPD90 and ERP of the left atrial myocardium, the shortening ability of the MAPD90 in relation to an increase in the simulation frequency was not maintained in the left atrial myocardium, there were differences between the left and right atrial myocardium, and so on, which we consider would provide the substrate for AF.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have also shown that there are differences between the right and left atria in refractoriness and APD, [11][12][13][14][15] which may be an important physiological factor in the maintenance of AF, and the effect of aging on these differences also needs to be further studied.…”
mentioning
confidence: 99%
“…Whole cell voltage-clamp studies in canine atrial cardiomyocytes showed that atrial tachycardia leads to a substantial reduction in I Ca-L density (24), and 60% reduction of I Ca-L in AF was reported in human atrial cardiomyocytes (38). There is also growing focus on the importance of electrophysiological heterogeneity between both atria in the initiation and maintenance of AF (11,18,21,32). In this study, we show that there are no significant differences in the protein level of the ␣ 1D Ca channel from the left and right atria, suggesting minor contribution of ␣ 1D I Ca-L in the interatrial ionic current heterogeneity.…”
Section: Discussionmentioning
confidence: 55%